A CROSS SECTIONAL SURVEY TO KNOW THE PREVALENCE OF NOCTURNAL ENURESIS AND ASSOCIATED COMORBIDITIES IN CHILDREN AGED 5 TO 18 YEARS (Journal of Pharmaceutical Negative Results, 2022)
Introduction: The present research was aimed to identify prevalence & associated comorbidities of nocturnal enuresis in children.Methods: Present study was a cross sectional survey, conducted in two government schools. The school, administration was briefed about this disease, its adverse impact on child’s school performance. Data collected was related to age, gender, some disease characteristics, and associated comorbidities. Questionnaire used had contact number of the hospital, some general instructions to help these children like restricted liquid intake in evening hours, regular frequent urination & maintenance of voiding diary. The permission to conduct the survey was granted by the schools. To maintain anonymity, to avoid embarrassment and to encourage maximum participation these were handed over to the class teachers who distributed these to the parents of all the students in next Parent teacher meeting. Children dropped these filled questionnaires in a box kept in common room.Results: Total 306 children were identified. Enuresis was commonest in age group 7-12 years. MNE was found in majority. Positive family history of enuresis & poor quality of sleep was present in 50.3% &32% children respectively. Functional constipation was found in 41.2% (126) & UTI in 8.8% (27) children. Only 18.9% (58) children were taken to a health care facility for NE. Parental punitive practices reported were humiliation and physical punishment in 83% &66.7% children.Conclusion: Nocturnal enuresis is a common under reported condition. Families and children are suffering instead of consulting a doctor parents’ resort to various punitive measures.